Climate-related risk disclosures and investors' risk perceptions – Evidence on the nuanced effects of financial and impact materiality - Neunsinger, Christof; Pager, Lena; Fischer, Thomas (46th Annual Congress of the European Accounting Association (EAA), 2024)

Do organizational capabilities affect the capital market indicators of firm resilience? An empirical analysis of voluntary disclosures in 10-K filings of S&P 1500 firms - Neunsinger, Christof; Pager, Lena; Fischer, Thomas (20th Annual Conference for Management Accounting Research (ACMAR), 2023)

Do organizational capabilities affect the capital market indicators of firm resilience? An empirical analysis of voluntary disclosures in 10-K filings of S&P 1500 firms - Neunsinger, Christof; Pager, Lena; Fischer, Thomas (45th Annual Congress of the European Accounting Association (EAA), 2023)

Gestaltung der Organisationalen Resilienz durch die Implementierung von SSOs - Fischer, Thomas; Neunsinger, Christof (75. Deutscher Betriebswirtschafter-Tag der Schmalenbach-Gesellschaft, 2021)

How do organizational capabilities affect capital market indicators of organizational resilience – An empirical analysis of voluntary disclosures in 10-K filings of S&P 1500 firms - Neunsinger, Christof; Pager, Lena; Fischer, Thomas (11th Empirical Research in Management Accounting & Control (ERMAC) Conference, 2022)

Klassische Pfade und innovative Konzepte: Wie Shared Services die Wettbewerbsfähigkeit von Unternehmen stärken - Brühl, Rolf; Eberle, Eckard; Fischer, Thomas; Haefs, Roland; Laux, Thomas; Neunsinger, Christof; Scheidemantel, Frank (2024)

Managing Customer Satisfaction: An Analysis of Digital Applications for Insurance Companies - Osterrieder, Katrin; Eckert, Christian; Neunsinger, Christof (25th Asia Pacific Risk and Insurance Association (APRIA), 2021)

Managing customer satisfaction: digital applications for insurance companies - Eckert, Christian; Neunsinger, Christof; Osterrieder, Katrin (Geneva Papers on Risk and Insurance: Issues and Practice, 2022)
Customer satisfaction management is increasing in importance within the insurance industry. In particular, to define a customer-oriented strategy, installing digital applications based on technologies, e.g. including artificial intelligence or cloud computing, ranks among the major strategic challenges. Against this background, the aim of this paper is to take an integrated perspective on managing customer satisfaction and the digital transformation. Towards this end, we identify and assess a set of digital applications, as a result of a comprehensive review of 106 academic papers and publications of the industry and supervisory authorities. We illustrate the opportunities to increase customer satisfaction and emphasise their impact on insurers at four major customer touch points: contract conclusion, contract modifications, the event of damage and further contacts. Our results are strategic measures to strengthen the position for sales and marketing, to simplify standard processes and to increase efficiency and interaction with the customer.
CRIS-Team WoS Importer:2022-02-18

Organisationale Resilienz: Begriffsverständnis und Gestaltungsaspekte für SSOs - Fischer, Thomas; Neunsinger, Christof (Arbeitskreis "Shared Services" der Schmalenbach-Gesellschaft, 2021)

Shared Services as Levers for Improving Competitiveness – Sustainability and Organizational Resilience - Fischer, Thomas; Neunsinger, Christof (77. Deutscher Betriebswirtschafter-Tag der Schmalenbach-Gesellschaft, 2023)

Sustainability Management and Reporting - An Opportunity (or a Threat) for the SSO? - Fischer, Thomas; Neunsinger, Christof (Arbeitskreis "Shared Services" der Schmalenbach-Gesellschaft, 2022)